Detonation nanodiamonds biofunctionalization and immobilization to titanium alloy surfaces as first steps towards medical application - Gonçalves, Juliana P. L.; Shaikh, Afnan Q.; Reitzig, Manuela; Kovalenko, Daria A.; Michael, Jan; Beutner, René; Cuniberti, Gianaurelio; Scharnweber, Dieter; Opitz, Jörg (Beilstein Journal of Organic Chemistry, 2014)
Due to their outstanding properties nanodiamonds are a promising nanoscale material in various applications such as microelectronics, polishing, optical monitoring, medicine and biotechnology. Beyond the typical diamond characteristics like extreme hardness or high thermal conductivity, they have additional benefits as intrinsic fluorescence due to lattice defects without photobleaching, obtained during the high pressure high temperature process. Further the carbon surface and its various functional groups in consequence of the synthesis, facilitate additional chemical and biological modification. In this work we present our recent results on chemical modification of the nanodiamond surface with phosphate groups and their electrochemically assisted immobilization on titanium-based materials to increase adhesion at biomaterial surfaces. The starting material is detonation nanodiamond, which exhibits a heterogeneous surface due to the functional groups resulting from the nitrogen-rich explosives and the subsequent purification steps after detonation synthesis. Nanodiamond surfaces are chemically homogenized before proceeding with further functionalization. Suspensions of resulting surface-modified nanodiamonds are applied to the titanium alloy surfaces and the nanodiamonds subsequently fixed by electrochemical immobilization. Titanium and its alloys have been widely used in bone and dental implants for being a metal that is biocompatible with body tissues and able to bind with adjacent bone during healing. In order to improve titanium material properties towards biomedical applications the authors aim to increase adhesion to bone material by incorporating nanodiamonds into the implant surface, namely the anodically grown titanium dioxide layer. Differently functionalized nanodiamonds are characterized by infrared spectroscopy and the modified titanium alloys surfaces by scanning and transmission electron microscopy. The process described shows an adsorption and immobilization of modified nanodiamonds on titanium; where aminosilanized nanodiamonds coupled with O-phosphorylethanolamine show a homogeneous interaction with the titanium substrate.
Keywords: biofunctionalization; carbon-nanomaterials; detonation nanodiamond; electrochemical immobilization; surface modification; titanium alloy